2022
DOI: 10.3389/fphar.2022.806869
|View full text |Cite
|
Sign up to set email alerts
|

Maackiain Modulates miR-374a/GADD45A Axis to Inhibit Triple-Negative Breast Cancer Initiation and Progression

Abstract: Breast cancer ranks as the leading cause of death in lethal malignancies among women worldwide, with a sharp increase of incidence since 2008. Triple negative breast cancer (TNBC) gives rise to the largest proportion in breast cancer-related deaths because of its aggressive growth and rapid metastasis. Hence, searching for promising targets and innovative approaches is indispensable for the TNBC treatment. Maackiain (MA), a natural compound with multiple biological activities, could be isolated from different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…A total of eight compounds, including flavonoids, anthraquinones, and triterpenoids, were identified from the HSF of KR extracts via LC-MS analysis ( Table 2 ). Among these, calycosin, aloe emodin, rhein, and maackiain reportedly exhibit effects against breast cancer [ 29 , 30 , 31 ], while asperuloside, orientin, vicenin-2, and kaempferitrin were proven to exhibit anti-tumor activity [ 32 , 33 , 34 , 35 , 36 ]. Additionally, 3-hydroxymorindone and rubiadin were found to occur in HSF through a comparison with reference compounds.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of eight compounds, including flavonoids, anthraquinones, and triterpenoids, were identified from the HSF of KR extracts via LC-MS analysis ( Table 2 ). Among these, calycosin, aloe emodin, rhein, and maackiain reportedly exhibit effects against breast cancer [ 29 , 30 , 31 ], while asperuloside, orientin, vicenin-2, and kaempferitrin were proven to exhibit anti-tumor activity [ 32 , 33 , 34 , 35 , 36 ]. Additionally, 3-hydroxymorindone and rubiadin were found to occur in HSF through a comparison with reference compounds.…”
Section: Resultsmentioning
confidence: 99%
“…They affect estrogen receptors, cellular signaling pathways, cell cycle, apoptosis, and steroid synthesis, and induce DNA damage in cancer cells [ 51 ]. Maackiain could suppress breast cancer cell proliferation, lesion formation, migration, and invasion [ 31 ]. Breast cancer cells were inhibited from invading and migrating by aloe emodin, which inhibited pro-tumorigenic cytokine expression [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…In cancer therapy, MK can hinder the proliferation, migration, invasion, and foci formation of triple-negative breast cancer cells and thus has a significant inhibitory effect on tumor growth. Furthermore, MK can induce apoptosis by reducing miR-374a, leading to an increase in GADD45α [ 88 ]. In in vitro studies, we found that 1 μM MK was not lethal to GBM cells but could significantly diminish the proliferation and migration of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Maackiain, a typical isoflavonoid, is extracted from traditional Chinese medicine peony root. Maackiain possesses antioxidative [ 18 ], antiseptic [ 19 ], antitumor [ 20 ], and immunoregulatory properties [ 21 ]. Maackiain has recently been reported to exhibit beneficial effects on preventing and improving diabetes mellitus-related metabolic disturbance [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, 10 μM Aβ 42 stimulation for 24 hours was selected as a condition to induce injury to PC12 cells for the following experiments. To determine the protective effects of Maackiain on cell injury induced by Aβ 42 , PC12 cells were pretreated with different doses of Maackiain(10,20, and 50 μM) six hours before 10 μM Aβ 42 stimulation. The results of CCk-8 and LDH activity assay showed that Maackiain prevented Aβ 42 -induced cell injury in a dose-dependent way (Figures1(c) and 1(d)).…”
mentioning
confidence: 99%